Albumin-based smart nanoplatform for ultrasound-mediated enhanced chemo‐sonodynamic combination therapy. (March 2023) - Zhang, Da-Gui; Chen, Biao-Qi; Pan, Yu-Jing; Liu, Hao; Shi, Yu-Hong; Chen, Lin-Fei; Kankala, Ranjith Kumar; Wang, Shi-Bin; Chen, Ai-Zheng
Graphical abstract: Highlights: An multifunctional nanoplatform (HIP NPs) was fabricated using a facile self-assembly and desolvation technology. HIP NPs possessed excellent tumor accumulation, desirable sonodynamic performance and negligible systematic toxicity properties. The released piceatannol could augment the sonodynamic therapy efficacy of HIP NPs via downregulating the expression level of HIF-1 α . Photoacoustic imaging-guided chemo‐sonodynamic combination therapy could be achieved towards tumor ablation. Abstract: As a novel reactive oxygen species (ROS)-mediated therapeutic modality, sonodynamic therapy (SDT) has recently received enormous attention due to the unique benefits of deep tissue penetration and insignificant side effects. However, the hypoxic microenvironment increases the tumor resistance to SDT, hindering its therapeutic efficacy. In this work, an ingenious nanoplatform was designed via a facile self-assembled strategy of human serum albumin (HSA, a biocompatible carrier), IR780 iodide (IR780, a sonosensitizer and an imaging probe), and piceatannol (PIC, an effective HIF-1 α inhibitor and a chemotherapeutic drug), to achieve combined therapy of enhanced SDT and chemotherapy. Under ultrasound irradiation, the as-formed HSA/IR780/PIC nanoparticles (HIP NPs) effectively generated ROS and accelerated the release of PIC from HIP NPs. In addition, the released PIC played a chemotherapeutic effect and effectively reduced hypoxia-mediated SDT resistance by downregulating the expression of HIF-1 α . Furthermore, compared to IR780, HIP NPs exhibited higher tumor accumulation, better imaging performance and lower systematic toxicity, ultimately achieving combined SDT and chemotherapeutic effects. Together, these findings demonstrate a promising nanoplatform to combat hypoxia-mediated SDT resistance and enhance the SDT efficacy. In addition, this proof-of-concept design of the nanoplatform may furnish a facile and effective strategy to construct a multifunctional nanoplatform for acquiring precise cancer theranostics.